2012
DOI: 10.3747/co.19.1177
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Cancer Care: A Canadian Perspective

Abstract: Canada is facing cancer crisis. Cancer has become the leading cause of death in Canada. Despite recent advances in cancer management and research, growing disparities in cancer care have been noticed, especially in socio-economically disadvantaged groups and under-served communities. With the rising incidence of cancer and the increasing numbers of minorities and of social disparities in general, and without appropriate interventions, cancer care disparities will become only more pronounced. This paper highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 28 publications
3
63
0
3
Order By: Relevance
“…Among patients with metastatic CRC, median survival in Greenland was similar to patients in Scandinavia: 17 vs. 15.8 months for patients treated with chemotherapy and 2 vs. 2.8 months for patients receiving best supportive care alone [20]. Despite a previous study in Greenland suggesting a significant diagnostic delay for patients living in remote areas outside Nuuk [6], and international research reporting on significant disparities in cancer-related outcomes in rural and remote areas [1013], we found no significant difference in stage distribution or survival rates between patients from Nuuk and patients living along the coastline outside Nuuk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Among patients with metastatic CRC, median survival in Greenland was similar to patients in Scandinavia: 17 vs. 15.8 months for patients treated with chemotherapy and 2 vs. 2.8 months for patients receiving best supportive care alone [20]. Despite a previous study in Greenland suggesting a significant diagnostic delay for patients living in remote areas outside Nuuk [6], and international research reporting on significant disparities in cancer-related outcomes in rural and remote areas [1013], we found no significant difference in stage distribution or survival rates between patients from Nuuk and patients living along the coastline outside Nuuk.…”
Section: Discussionmentioning
confidence: 92%
“…Data from a recent study in Greenland evaluating 113 CRC patients indicated that patients living on the coastline were exposed to a significant diagnostic delay compared to their counterparts in Nuuk [9]. Geographical remoteness has also been shown to cause disparities in treatment patterns and outcome for cancer patients living in Australia, USA and Canada [1013]. Globally, survival is generally better in countries with good access to specialised care [14].…”
Section: Introductionmentioning
confidence: 99%
“…[34] Increasingly, however, health disparities are being documented among cancer survivors who live in rural and remote settings, those with lower socioeconomic status, or who are older, with advanced disease at diagnosis, and in Indigenous and ethnic minority groups, as well as immigrants. [34567891011]…”
Section: Canadian Perspectives On Cancer Health Disparitiesmentioning
confidence: 99%
“…[51213] Efforts to address cancer disparities in Canada largely have been aimed at improving access to care, such as through the introduction of nurse navigator roles.…”
Section: Canadian Perspectives On Cancer Health Disparitiesmentioning
confidence: 99%
“…For instance, recent estimates indicate that tobacco-related illness costs Canadians CA$4.4 billion in direct health care costs, with an estimated social cost of CA$17 billion per year 29 . Differential exposure to modifiable determinants can result in differential rates of cancer incidence and mortality 30 . Notably, health gradients can be related to poverty, rural or remote location, and language and cultural barriers in various high-risk populations, including socioeconomically disadvantaged people, rural residents, and aboriginal, ethnic minority, and immigrant groups.…”
Section: Primary Prevention: Aiming At the Achilles Heelmentioning
confidence: 99%